Towards conceptualising business and public administration research augmented by analysing the physical research context, the research problem, and the research knowledge gap - Wotela, K. (IPADA, 2019)
Before anything else, a sound research report or dissertation or thesis is its conceptualisation in which we spell out 'what' research we want to do and 'why'. Other than interrogation of the fundamentals – that is, the research title, research problem statement, research purpose statement, and research questions as well as where applicable the accompanying research hypotheses or research propositions- research conceptualisation requires a structured interrogation of literature to strengthen its case and the research focus. This literature interrogation should provide for a thorough analysis of the research physical context or setting, the research problem, and the research knowledge gap. There are several guides on research conceptualisation and literature interrogation meant to assist research students and novices. But guides do not work in all cases and situations because of different contexts and, therefore, leaving room for improvement and additional guides such as this paper. Using information compiled from examiners' reports of our research students and discussions with research students and colleagues, we propose a structured approach to research conceptualisation that is augmented by a thorough analysis of the research physical context or setting, the research problem, and the research knowledge gap. Though research conceptualisation resides in the 'introduction to the research' component of a research, ideally its interrogation is part of the 'conceptual framework' component - which we narrowly call the literature review. Therefore, as part of literature review, we should explicitly interrogate academic and non-academic literature on (i.) the physical context or setting where the research will take place and (ii.) the research problem. A thorough research problem analysis requires systems thinking and the theory of constraint to guide the interrogation of literature. These tools provide for going beyond the 'he said, she said' literature review write-ups that are evident in most student write-ups. Further, research conceptualisation is incomplete unless we explicitly interrogate empirical or primary research literature to expose the (iii.) research knowledge gap. When undertaking a research knowledge gap analysis, we should not only focus on the empirical research results and research findings. Instead, we should also interrogate research strategies, designs, procedure and methods that such studies applied so that we also start reflecting on which research procedure and methods we will apply to our research.
The 4th Annual International Conference on Public Administration and Development Alternatives 03 - 05 July 2019, Southern Sun Hotel, OR Tambo International Airport, Johannesburg, South Africa
Keywords: Conceptual framework; Literature review; Research conceptualisation; Research knowledge gap analysis; Research problem analysis; Research physical context; Setting analysis; Proposal writing in research; Management science; Research